PENINGKATAN MOTIVASI BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI EKOSISTEM MELALUI PENERAPAN MODEL INKUIRI TERBIMBING - Hermayani, Anisa Zahra; Dwiastuti, Sri; Marjono, Marjono (Bioedukasi Jurnal Pendidikan Biologi, 2015)
The purposes of this research are to increase students learning motivation and critical thinking skills of class X MIA 5 SMA Batik 1 Surakarta through the implementation mode of guided inquiry. This research is a Classroom Action Research with 2 cycles of action. Each cycle consisting of 4 phases which are planning, acting, observing, and reflecting. Observational data obtained from the observation sheet, questionnaire, and test. Technical analysis of data is descriptive qualitative. Data validation is used triangulation method.Â  The result of this research shows that with the implementation model of guided inquiry learning could increase learning motivation and critical thinking skills in Biological learning. Itâs based on the result of observation sheet, questionnaire, and test. Average percentage for each aspect of learning motivation pre-cycle areÂ  45,4%, first cycle are 65,08% (increase 19,68%), and last cycle 75,17% (increase 10,09%), while percentage for each aspect of critical thinking skills pre-cycle are 34,17%, first cycle 51,10% (increase 16,93%), and last cycle are 61,73% (increase 10,63%). This it can be concluded that the implementation model of Guided Inquiry learning could increase learning motivation and critical thinking skills of students class X MIA 5 SMA Batik 1 Surakarta class year 2014/2015.Kata kunci: Inkuiri terbimbing, motivasi belajar, keterampilan berpikir kritis